2019
DOI: 10.1016/j.jen.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Symptoms in Women and Men Presenting to the Emergency Department With Suspected Acute Coronary Syndrome

Abstract: Introduction: More than 5.5 million patients present to emergency departments (EDs) in the United States annually for potential acute coronary syndrome (ACS); however, diagnosing ACS remains a challenge in the EDs. Our aim was to describe the quality of symptoms (chest discomfort/pain description, location/radiation, and overall symptom distress) reported by women and men ruled-in and ruled-out for ACS in the EDs. Methods: The sample consisted of 1,064 patients presenting to the EDs with symptoms that triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…Based on the pain location, it was found that males with ACS tend to experience pain in the left or middle chest compared to female patients, while females felt more pain in the chest area radiating to the neck and chin. This data is directly proportional to previous studies, [16][17][18] that demonstrated pain in the middle part of chest is more experienced by males with a p<0.01 and female patients experience pain in form of radiations to the neck, chin, and shoulder area with a p<0.01. The difference in symptomatic manifestation in males and females with ACS is due to the process of chest pain transmission mechanism mediated by sympathetic and vagal nerves activation.…”
Section: Resultssupporting
confidence: 80%
“…Based on the pain location, it was found that males with ACS tend to experience pain in the left or middle chest compared to female patients, while females felt more pain in the chest area radiating to the neck and chin. This data is directly proportional to previous studies, [16][17][18] that demonstrated pain in the middle part of chest is more experienced by males with a p<0.01 and female patients experience pain in form of radiations to the neck, chin, and shoulder area with a p<0.01. The difference in symptomatic manifestation in males and females with ACS is due to the process of chest pain transmission mechanism mediated by sympathetic and vagal nerves activation.…”
Section: Resultssupporting
confidence: 80%
“…ACS is a time-critical condition, which means delays in diagnosis and treatment of the disease can upsurge the risk of heart muscle damage, leading to increased morbidity and mortality [ 1 , 5 , 6 ]. Several patient and service level factors have been identified as affecting the timely diagnosis and treatment of ACS; among them are the patient’s hesitation and delay in seeking medical care is a key factor [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several patient and service level factors have been identified as affecting the timely diagnosis and treatment of ACS; among them are the patient’s hesitation and delay in seeking medical care is a key factor [ 7 ]. Mirzaei et al found that lack of recognition of ACS symptoms, the discrepancy between actual and expected symptoms, and discrepancy between current symptoms and previous experience of the disease are some factors contributing to delay in timely treatment seeking [ 6 ]. Also, a lack of previous experience of ACS affects how the symptoms are interpreted and acted upon by patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 ACS is often an elusive and challenging diagnosis that depends on rapid assessment, triage, and risk stratification. 11 Emergency nurses are charged with identifying and recognizing quickly individuals who present with symptoms suggestive of ACS. Symptom recognition and timely reperfusion minimize ischemic time, salvage the myocardium, preserve left ventricular function, and improve survival.…”
mentioning
confidence: 99%